System dynamics for social good - Paulo Gonçalves (Production)
Abstract Paper aims This paper portrays three examples of system dynamics modes applied to social good. Originality System dynamics has a strong tradition of applied research addressing complex social issues ranging from world and urban dynamics to the spread of infectious diseases. System dynamics can provide insight and inform long-term policy in complex social systems. This paper describes system dynamics applications in three important social challenges facing humanity. Research method In this article, we present three applications of system dynamics research addressing important social challenges, such as HIV/AIDS policy, the eradication of infectious diseases, and capacity building at humanitarian organizations. Main findings The examples illustrate how system dynamics can effectively capture key elements of complex dynamic systems allowing managers to understand the behavior of such environments over time. Implications for theory and practice This paper contributes to Jay Forrester's bold vision of aiming system dynamics to model important social challenges faced by humanity.